MANGKIKI’: Kajian Misi Transformasi terhadap Budaya Mangkiki’ di Kalangan Penganut Aluk Toyolo di Mamasa - D, Yuliana; Bamba, Arruan; Maviana, Anggriel (Institut Agama Kristen Negeri Toraja, 2024)
Abstract: This study delves into the transformative mission of the church in the Aluk Toyolo culture of Mamasa about ritual of